Hair Cell Generation in Cochlear Culture Models Mediated by Novel γ-Secretase Inhibitors - Erni, Silvia T.; Gill, John C.; Palaferri, Carlotta; Fernandes, Gabriella; Buri, Michelle; Lazarides, Katherine; Grandgirard, Denis; Edge, Albert S. B.; Leib, Stephen L.; Roccio, Marta (Frontiers in Cell and Developmental Biology, 2021)
Sensorineural hearing loss is prevalent within society affecting the quality of life of 460 million worldwide. In the majority of cases, this is due to insult or degeneration of mechanosensory hair cells in the cochlea. In adult mammals, hair cell loss is irreversible as sensory cells are not replaced spontaneously. Genetic inhibition of Notch signaling had been shown to induce hair cell formation by transdifferentiation of supporting cells in young postnatal rodents and provided an impetus for targeting Notch pathway with small molecule inhibitors for hearing restoration. Here, the oto-regenerative potential of different γ-secretase inhibitors (GSIs) was evaluated in complementary assay models, including cell lines, organotypic cultures of the organ of Corti and cochlear organoids to characterize two novel GSIs (CPD3, CPD8). GSI-treatment induced hair cell gene expression in all these models and was effective in increasing hair cell numbers, in particular outer hair cells, both in baseline conditions and in response to ototoxic damage. Hair cells were generated from transdifferentation of supporting cells. Similar findings were obtained in cochlear organoid cultures, used for the first time to probe regeneration following sisomicin-induced damage. Finally, effective absorption of a novel GSI through the round window membrane and hair cell induction was attained in a whole cochlea culture model and in vivo pharmacokinetic comparisons of transtympanic delivery of GSIs and different vehicle formulations were successfully conducted in guinea pigs. This preclinical evaluation of targeting Notch signaling with novel GSIs illustrates methods of characterization for hearing restoration molecules, enabling translation to more complex animal studies and clinical research.